2011
DOI: 10.1007/s10495-011-0661-6
|View full text |Cite
|
Sign up to set email alerts
|

The MCP-1/CCR2 axis in podocytes is involved in apoptosis induced by diabetic conditions

Abstract: Previous studies have demonstrated the importance of monocyte chemoattractant protein-1 (MCP-1) in the pathogenesis of diabetic nephropathy in terms of inflammation, but the direct role of the MCP-1/CCR2 system on podocyte apoptosis under diabetic conditions has never been explored. In vitro, mouse podocytes were exposed to a medium containing 30 mM glucose (HG) with or without CCR2 siRNA or CCR2 inhibitor (RS102895). Podocytes were also treated with MCP-1 or TGF-β1 with or without anti-TGF-β1 antibody, CCR2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 40 publications
(67 reference statements)
3
29
0
1
Order By: Relevance
“…Some debate exists about which mechanism, namely podocyte apoptosis or detachment, is quantitatively more important for podocyte loss in glomerulopathies such as diabetic nephropathy. Although TGF-β has been shown to induce podocyte apoptosis in vitro and in vivo, the apoptosis rates detected in vivo are low (Nam et al 2011). The studies of Wharram et al (2005) have demonstrated that high rates of podocyte loss are necessary to cause glomerular scarring: depletion of podocytes by up to 40% results in only minor changes in the glomerular structure and moderate proteinuria without measurable changes in renal function, with podocyte depletion of over 40% being required before a detectable decrease in renal function can be observed.…”
Section: Effect Of Tgf-β On Podocytesmentioning
confidence: 99%
“…Some debate exists about which mechanism, namely podocyte apoptosis or detachment, is quantitatively more important for podocyte loss in glomerulopathies such as diabetic nephropathy. Although TGF-β has been shown to induce podocyte apoptosis in vitro and in vivo, the apoptosis rates detected in vivo are low (Nam et al 2011). The studies of Wharram et al (2005) have demonstrated that high rates of podocyte loss are necessary to cause glomerular scarring: depletion of podocytes by up to 40% results in only minor changes in the glomerular structure and moderate proteinuria without measurable changes in renal function, with podocyte depletion of over 40% being required before a detectable decrease in renal function can be observed.…”
Section: Effect Of Tgf-β On Podocytesmentioning
confidence: 99%
“…17,19 Recently, we also found that MCP-1 directly induced podocyte apoptosis. 18 In addition, MCP-1 itself induced intercellular adhesion molecule-1 and fibronectin expression in cultured mesangial cells. 14 Moreover, some investigators have provided evidence that MCP-1 may be directly involved in ECM synthesis using animal models of experimental glomerulonephritis 15 and diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 97%
“…18 The band densities were measured using TINA image software (Raytest, Straubenhardt, Germany), and the changes in the optical densities of bands from the treated groups relative to NG cells or C peritoneum were used in the analysis.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Lentivirus vectors and liposomes are widely applied for the transduction of siRNA into different types of cultured renal cells. For example, silencing ccr2 using its siRNA delivered by a lentivirus significantly ameliorated MCP-1 induced podocyte apoptosis under diabetic conditions [23]. Similarly, degradation of FoxO1 by transfecting its siRNA via lentiviral vectors overrode the limited cell cycle and stimulated proliferation of glomerular mesangial cells [24].…”
Section: Sirna Deliverymentioning
confidence: 99%